Influence of ethanol on dentin roughness, surface free energy, and interaction between AH Plus and root dentin - Carlos Augusto de Morais Souto Pantoja; Diogo Henrique da Silva; Adriana de Jesus Soares; Caio Cezar Randi Ferraz; Brenda Paula Figueiredo de Almeida Gomes; Alexandre Augusto Zaia; José Flávio Affonso de Almeida (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study aimed to evaluate the influence of different ethanol concentrations on dentin roughness, surface free energy, and contact angle between AH Plus and the root canal dentin. One hundred human maxillary anterior teeth were split longitudinally and 200 dentin specimens were polished to make the surface flatter and smoother. An acrylic bar was positioned between two dentin specimens and impression material was added to create a block, simulating an instrumented root canal space. Specimens were removed from the mold and cleaned in an ultrasonic bath for 10 min. Thereafter, dentin specimens were divided into four groups (n = 50) according to the drying methods used: a) wet: vacuum only, b) paper points: vacuum + absorbent paper points, c) 70% alcohol: 70% alcohol (1 min) + vacuum + absorbent paper points, and d) 100% alcohol: 100% alcohol (1 min) + vacuum + absorbent paper points. A rugosimeter and a goniometer were used to verify the roughness (Ra) and to measure the surface free energy and the contact angle between the AH Plus sealer and the root canal dentin. ANOVA and Tukey tests (α = 0.05) were used for statistical analysis. The 70% and 100% ethanol groups showed significantly decreased roughness as well as increased surface free energy in the root canal dentin when compared to the wet and paper point groups. In addition, ethanol significantly reduced the contact angle between the AH Plus sealer and the root canal dentin. Ethanol solutions (70% and 100%) provide better wettability of AH Plus sealer on dentin surfaces.